2012
DOI: 10.1002/ijc.27456
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin delays progression of pancreatic lesions to carcinoma by regulating PI3/AKT signaling in p48Cre/+ LSL‐KrasG12D/+ mice

Abstract: Pancreatic cancer is the one of most common causes of cancer deaths and has the worst prognosis. Clinical observational studies suggest that statins may reduce the risk of pancreatic cancer. The chemopreventive efficacy of the statin atorvastatin (Lipitor®) and the role of the phosphatidyl-inositol 3-kinase(PI3/AKT) signaling pathway were evaluated for the progression of pancreatic intraepithelial neoplasms (PanINs) to pancreatic ductal adenocarcinoma (PDAC) in conditional p48Cre/+-LSL-KrasG12D/+ transgenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 43 publications
4
70
0
1
Order By: Relevance
“…Simvastatin and atorvastatin have been shown to significantly delay the progression of PanIN lesions to PDAC and to inhibit PDAC growth in conditional K-Ras mutant mice (57,58). In one study, treatment with atorvastatin resulted in significantly downregulated expression of components of the Ras/MAPK, phosphoinositide 3-kinase (PI3K)/Akt and nuclear factor-κB (NF-κB) signaling pathways, including Akt, phosphorylated (p) Akt, purinergic receptor P2X7, RhoA, pERK, cyclin dependent kinase 2, cyclin D1, β-catenin, cyclin E, survivin, caveolin-1, granulocyte-macrophage colony-stimulating factor, cyclooxygenase-2 (COX-2), and interleukin (IL)-2, -6 and -12 in vivo ( Fig.…”
Section: Mechanisms Of Action and Evidence Of Antitumor Effects Of Stmentioning
confidence: 99%
“…Simvastatin and atorvastatin have been shown to significantly delay the progression of PanIN lesions to PDAC and to inhibit PDAC growth in conditional K-Ras mutant mice (57,58). In one study, treatment with atorvastatin resulted in significantly downregulated expression of components of the Ras/MAPK, phosphoinositide 3-kinase (PI3K)/Akt and nuclear factor-κB (NF-κB) signaling pathways, including Akt, phosphorylated (p) Akt, purinergic receptor P2X7, RhoA, pERK, cyclin dependent kinase 2, cyclin D1, β-catenin, cyclin E, survivin, caveolin-1, granulocyte-macrophage colony-stimulating factor, cyclooxygenase-2 (COX-2), and interleukin (IL)-2, -6 and -12 in vivo ( Fig.…”
Section: Mechanisms Of Action and Evidence Of Antitumor Effects Of Stmentioning
confidence: 99%
“…Hence, developing novel strategies to delay or inhibit progression of pancreatic cancer targeting CSCs are warranted. The K-rasG12D genetically engineered mouse (GEM) is an excellent model that shows the development of lesions closely resembling human PanIN's with progression to PDAC and it has been used successfully for chemoprevention studies [5,8,[72][73][74][75][76][77][78] . We have shown that licofelone, a dual COX-5-LOX inhibitor, exhibits chemopreventive efficacy against pancreatic cancer in p48…”
Section: Role Of Pancreatic Cscs In Prevention and Treatmentmentioning
confidence: 99%
“…The extent of the anti-cancer effects has been shown to vary depending on model and type of statin used [24][25][26][27][28][29][30]. Thus, we evaluated which of the seven currently available statins may be most effective for PHEO/PGL treatment.…”
Section: Introductionmentioning
confidence: 99%